FORMULASI GEL EKSTRAK ETANOL KULIT BUAH MANGGIS (Garcinia mangostana L.) DENGAN VARIASI GELLING AGENT SEBAGAI SEDIAAN LUKA BAKAR - Lena Maulina; Nining Sugihartini (Pharmaciana, 2015)
Pericarp of mangosteen is waste that has been shown have efficacy as an anti-inflammatory and accelerate the proliferation of fibroblasts. Therefore  it need to be formulated in the form of gel to make easy in the use of preparation. It is needed an appropriate gelling agent to produce the good character of gel. This research aimed to know the type of the gelling agent who has the physical properties gel and the activity of the best treat burns. There are three gel formula designed with various  type of  the gelling agent i.e. FI (the gelling agent carbopol); FII (the gelling agent CMC na); FIII (the gelling agent tragacanth). The obtained gels were tested organoleptic, of homogeneity, pH, spreadibility, adhesivity, consistency and the effect of healing burns in nine groups. The collected data were analyzed statistically using SPSS version 16 with kolmogorov-smirnov and continued one way ANOVA or  Kruskal-Wallis, with level of trust 95 %. The results show that all formula mixed homogeneous gel. Formula I have a pH 3,5 while formula II and III having a ph 5 (p < 0,05). The greater spreadibility given by formula III (p < 0,05) and the longest time of adhesivity given by formula II (p < 0,05). The best activity of wound healing given by formula I (p > 0,05). Based on the result show that type of gelling agent can influence the physical properties and activity in the treating burns. Type of gelling agent that show the best physical properties is CMC Na.